ЕТНОНАЦІОНАЛЬНИЙ КОНТЕКСТ ФІНАНСОВИХ ВІДНОСИН В УКРАЇНСЬКОМУ ПІВНІЧНОМУ ПРИАЗОВ’Ї (УПП) (Zaporizhzhia Historical Review, 2021)
The necessity of improvement of territorial administrative structure and budget relations, the extension of financial basis of local self-government is actualized in order to solve common and ethnically specific for problems of territorial communities of both types, which touch upon innovative development of economic resources of the areas, and which are in social sphere such as satisfaction of educational, national, cultural and other community needs according to Ukrainian Northern Pryazov’ya materials.